2012
DOI: 10.1002/anie.201206227
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Emitting Electrochemical “Swimmers”

Abstract: Swimmer in the dark: propulsion of a conducting object is intrinsically coupled with light emission using bipolar electrochemistry. Asymmetric redox activity on the surface of the swimmer (black bead) causes production of gas bubbles to propel the swimmer in a glass tube with simultaneous electrochemiluminescence (ECL) emission to monitor the progress of the swimmer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(111 citation statements)
references
References 56 publications
3
108
0
Order By: Relevance
“…Detection limits are normally on the order of millimoles, although much lower levels have been reported in certain systems (112). Through direct observation of motion under a microscope, it has been shown that the movement of nano-and micromotors can be coupled with other phenomena, such as emission of light (113), which may lead to new detection methods for motor motion, and hence chemical sensing.…”
Section: Chemical Sensing With Synthetic Motorsmentioning
confidence: 99%
“…Detection limits are normally on the order of millimoles, although much lower levels have been reported in certain systems (112). Through direct observation of motion under a microscope, it has been shown that the movement of nano-and micromotors can be coupled with other phenomena, such as emission of light (113), which may lead to new detection methods for motor motion, and hence chemical sensing.…”
Section: Chemical Sensing With Synthetic Motorsmentioning
confidence: 99%
“…Bipolar electrochemistry also allows asymmetric particles to be synthesised by performing electrodeposition in different systems, such as carbon nanotubes and spherical microparticles . It also allows the motion of small objects to be controlled through the activation of micro‐ or nanomotors, allowing translational or rotational displacements …”
Section: Introductionmentioning
confidence: 99%
“…Because of charge neutrality during bipolar electrochemistry, water or a sacrificial molecule must be oxidized simultaneously at the anodic pole, generating oxidation products such as O 2 . In this case, such sacrificial molecules are [Ru(bpy) 3 2+ ] and TPrA, leading to the generation of ECL emission for future analytical applications . This principle was used on a latter report for dynamic glucose sensing.…”
Section: Janus Micromotors For (Bio)‐electrochemistry “On the Move”mentioning
confidence: 96%